2019
DOI: 10.1002/jcb.27899
|View full text |Cite|
|
Sign up to set email alerts
|

SNHG15 functions as a tumor suppressor in thyroid cancer

Abstract: Small nucleolar RNA host gene 15 (SNHG15) has been suggested to be overexpressed, and function as an oncogenic long noncoding RNA (lncRNA) in various types of human malignancies. However, the expression status and function of SNHG15 were still unknown in thyroid cancer. In our study, we assessed the expression status and clinical value in thyroid cancer samples, and explored the effect of SNHG15 on thyroid cancer cell proliferation, migration, and invasion. In results, SNHG15 expression was downregulated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…Growing evidences show lncRNAs exert important roles in the development and progression of various cancers, including HCC. [17][18][19] For example, lncRNA LINC00461 is upregulated in HCC and promotes cancer cell proliferation and invasion through miR-149-5p/ LRIG2 pathway. 20 LncRNA PVT1 regulates HCC progression via promoting autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidences show lncRNAs exert important roles in the development and progression of various cancers, including HCC. [17][18][19] For example, lncRNA LINC00461 is upregulated in HCC and promotes cancer cell proliferation and invasion through miR-149-5p/ LRIG2 pathway. 20 LncRNA PVT1 regulates HCC progression via promoting autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with non‐cancerous TC samples, the expression level of SNHG15 was lower in TC tissue samples . Low expression level of SNHG15 was identified to closely associate with age, pathology classification, clinical stage, tumour size and distant metastasis in TC patients . However, current evidences mainly focus the overexpression of SNHG15 in most cancers.…”
Section: Expression Pattern Functions and Clinical Potentials Of Snhmentioning
confidence: 97%
“…Expression profile data of various cancers from The Cancer Genome Atlas (TCGA) data set showed that only TC specimens displayed lower levels of SNHG15 expression . Liu et al validated the expression status of SNHG15 in a cohort of 40 paired TC tissues and adjacent non‐tumour samples using qRT‐PCR assay . Compared with non‐cancerous TC samples, the expression level of SNHG15 was lower in TC tissue samples .…”
Section: Expression Pattern Functions and Clinical Potentials Of Snhmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the research of Morvarid Saeinasab et al well elucidated that SNHG15 could facilitate cell proliferation, invasion and drug resistance in colorectal cancer functioned as a bifunctional MYC-regulated noncoding locus encoding a lncRNA by interacting with AIF. Similarly, Jiang et al demonstrated that in colon cancer, SNHG15 promoted tumor progression via stabilizing transcription factor Slug [18,19].However, as a tumor suppressor, only Liu et al reported that SNHG15 was downregulated in thyroid cancer tissue samples and cells and its inhibited expression positively enhanced cell proliferation, migration, invasion in vitro [20].…”
mentioning
confidence: 99%